Art and Philosophy: Harmony of Giring-Giring Dance, Manganjan Dance, Tambun Bungai Dance of Kalimantan Tengah - Lelunu, Sapta; Putri , Kesia Rosalina; Daniel; Olivia, Nia; Simanjuntak, Nova Lady (Indonesian Scientific Publication, 2023)
The possibility of tradition collaborating with dance, music and performance art is an amazing art. However, it becomes problematic if the space to perform one of the parts of tradition, namely dance as an art or work in certain regions or localities, is still minimal. Either from the history of dances from certain regions, for example Central Kalimantan, especially the Ma'anyan Dayak community, or the method of usage or meaningful values in the form of ribut rukun, togetherness, care and exploration space. This research method uses a literature review that examines the results of previous studies as secondary sources, online media, and accompanying photos of dances originating from Central Kalimantan. The findings show that the Dayak Giring-Giring dance, Manganjan Dance and Tambun Bungai Dance have a variety of cultural richness, the meaning of friendship, as well as a rich history that must get space from generation to generation to the global community as a cultured, dignified, valuable and communal dance.